Bioaccumulation of Heavy Metals Pb, Cd And Zn on Bentos in the Estuary of Porong River Sidoarjo - Yudita Prihatini Puji Rahma Sari; Barlah Rumhayati; Arie Srihardyastutie (Natural B, Journal of Health and Environmental Sciences, 2017)
This research is done to know the influence of sort and size of biota, pH dan Salinity of water body toward Bioconcentration Factor (BFC) heavy metal, and protein characterization in biota contaminated with heavy metal. Water sampling, biota and sediment are done in two locations in estuary River Porong i.e. estuary watery nearby river and estuary nearby sea. The parameter of water circumstance employed is pH and salinity. The analysis of metal in water sample and biota is done after destruction uses aqua regia. The fraction of metal which is easily switched in metal sediment is analyzed after extraction uses acetate acid. The concentration of metal is analyzed with spectrophotometer of atom absorptivity. Characterization of protein in biota sample is done through electrophoresis employing SDS-PAGE. The result of this research is seen that Sergestide(shrimp) and Corbulidae(shellfish) possess the same big ability in accumulating metal Pb, Cd and Zn. Biota with big size (>1cm) has BCF higher than biota with small size(<1cm). pH and salinity of water body does not influence BCF value. System of biota defense contaminated with heavy metal is marked by protein hsp40(35 kDa), hsp60(50kDa) and hsp90(90kDa).